If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5)(2x + -6) = 0 Reorder the terms: (5 + x)(2x + -6) = 0 Reorder the terms: (5 + x)(-6 + 2x) = 0 Multiply (5 + x) * (-6 + 2x) (5(-6 + 2x) + x(-6 + 2x)) = 0 ((-6 * 5 + 2x * 5) + x(-6 + 2x)) = 0 ((-30 + 10x) + x(-6 + 2x)) = 0 (-30 + 10x + (-6 * x + 2x * x)) = 0 (-30 + 10x + (-6x + 2x2)) = 0 Combine like terms: 10x + -6x = 4x (-30 + 4x + 2x2) = 0 Solving -30 + 4x + 2x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-15 + 2x + x2) = 0 Factor a trinomial. 2((-5 + -1x)(3 + -1x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-5 + -1x)' equal to zero and attempt to solve: Simplifying -5 + -1x = 0 Solving -5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = 0 + 5 -1x = 0 + 5 Combine like terms: 0 + 5 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {-5, 3}
| (2x^2+7x+10)-(x^2+2x-9)= | | 20a^2-25a=5a | | 8x+2+46=92 | | 6x+31=16x+79 | | 9x-18=x+40 | | 9x+3+61=80 | | 97x+28=55 | | (n+6)(n-9)=26 | | 6(3x-5)+2(3x-5)-8(3x-5)= | | 3x+0=-15 | | 1x+36+64=80 | | 2x^2(4x^3-3x^2+6x)= | | 7+5p-4=9p+21-7p | | 1-q/Q=Q-q/Q | | x+0=8 | | 63x-1+24=31 | | 31/3+11/2 | | 2/3y+10=y/3+36/5 | | 5p+3/2=9 | | 7.2x+6.5=15.5 | | -2a^3+5a^2-a=2 | | 8x+2+44=110 | | 3x^2-28x+20=0 | | (x)+(1/3)(x)=60 | | -2p-4=-9 | | 137+16.5(x)=465 | | 137+16.5(x)=399 | | 9/3+2=5 | | 2x(x+6y+4z)= | | 6p+19p=150 | | 3(-3/4) | | x+3/2=14 |